Simple renal cyst and renal dysfunction: A pilot study using dimercaptosuccinic acid renal Scan. Issue 8 (August 2016) - Kwon, Taekmin; Lim, Bumjin; You, Dalsan; Hong, Bumsik; Hong, Jun Hyuk; Kim, Choung‐Soo; Jeong, In Gab
Abstract: Aim: Little is known about the association between renal cyst and renal dysfunction. We evaluated the deterioration of renal function in patients with unilateral, large, simple renal cysts. Methods: Fifty patients with unilateral, simple renal cysts measuring ≥ 4 cm (cyst group) and 50 kidney donors (control group) were enrolled. Dimercaptosuccinic acid (DMSA) renal scans were performed to calculate split renal function. The differences between split renal function were calculated and compared. Clinical factors affecting decreased renal function in the cyst group were assessed. Results: The mean age of the patients in the cyst group was higher than the control group (59.1 vs 39.2 years; P = 0.001). Patients with renal cysts tended to be diagnosed with hypertension ( P = 0.001), However, the two groups did not significantly differ in terms of the other characteristics. The median cyst size was 7.2 cm (range, 4.5–14.2), and 31 of the 50 patients (60.2%) in the cyst group demonstrated decreased renal function in the cystic kidney units (median: 5.8%; range, 0.2–33). Although there were no differences in split renal function (50.1% vs 49.9%; P = 0.629) in the control group, the relative renal function of the cystic kidney units were significantly lower than the contralateral kidney units in the cyst group (48.3% vs 51.7%; P = 0.001). The decrease in relative renal function (>8%) in the cystic kidney units was associated with a higher serum uric acid levels and higher RENAL complexity ( P = 0.035 and P = 0.007, respectively). Conclusion: A significant proportion of unilateral, large, simple renal cysts are associated with decreased relative renal function on DMSA renal scans. Summary at a Glance: In this case control study, the differences between split renal function were compared between 50 patients with large unilateral simple renal cyst (4 cm or above) and 50 kidney donors. DMSA renal scans showed that a significant proportion of large unilateral simple renal cysts are associated with decreased relative renal function. The effect of intervention on the renal function in this group of patients would require further study.